1973
DOI: 10.1159/000122129
|View full text |Cite
|
Sign up to set email alerts
|

Pars Intermedia and Pars Distalis:Two Sites of ACTH Production in the Rat Hypophysis

Abstract: Pars intermedia and pars distalis of the rat hypophysis were examined, following experimentally induced alterations in ACTH secretion. The concentration of ACTH in the pars inter-media is considerably greater than that in the pars distalis. At 1 month after adrenalectomy, the ACTH concentration in the pars distalis increased 3-fold, while that in the pars intermedia remained unchanged. Following chronic administration of cortisol, the ACTH concentration in the pars distalis fell to 27% of the control, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 18 publications
(26 reference statements)
3
26
0
Order By: Relevance
“…A common biochemical origin of ACTH, <x-MSH, /3-LPH and /3-END is suggested by their unique tissue location within rat pars intermedia [Howe, 1973;Kraicer et al, 1973;LaBella et al, 1976;Pelletier et al, 1977;Bloom et al, 1977], as well as by the presence here of a 31,000 dalton precursor molecule [Mains et al, 1977] Howe andThody [1969, 1970] have re ported that lesions of the PVN of the hypo thalamus, or administration of hypertonic sa line in place of drinking water, induce a rise in neurointermediate lobe MSH. In contrast, Taleisnik et al [1967Taleisnik et al [ , 1972 found a reduction in pituitary MSH activity following these pro cedures.…”
Section: Discussionmentioning
confidence: 99%
“…A common biochemical origin of ACTH, <x-MSH, /3-LPH and /3-END is suggested by their unique tissue location within rat pars intermedia [Howe, 1973;Kraicer et al, 1973;LaBella et al, 1976;Pelletier et al, 1977;Bloom et al, 1977], as well as by the presence here of a 31,000 dalton precursor molecule [Mains et al, 1977] Howe andThody [1969, 1970] have re ported that lesions of the PVN of the hypo thalamus, or administration of hypertonic sa line in place of drinking water, induce a rise in neurointermediate lobe MSH. In contrast, Taleisnik et al [1967Taleisnik et al [ , 1972 found a reduction in pituitary MSH activity following these pro cedures.…”
Section: Discussionmentioning
confidence: 99%
“…In this way it is possible to confirm the existence of peaks of biological ACTH activity that coincide with each peak of immunological ACTH activity. The ACTH activity in tumor cell extracts and tumor cell tissue culture medium can be grouped into three molecular weight classes: molecular weight 20,000-30,000 (20-30k ACTH), molecular weight 6500-9000 (6.5-9k ACTH), and molecular weight 4000-5500 (4-5.5k ACTH) (45 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), mice (10,13), cows (3,4,14), pigs (4,15), and rabbits (4) contain ACTH activity. In contrast to the distribution of ACTH between these two lobes, growth hormone, thyroid stimulating hormone, prolactin, and the gonadotropins are found only in the anterior lobe (1,2 (2,9,10), but a clean separation of these lobes is difficult (8), so the amount of ACTH (2,3,12).…”
mentioning
confidence: 99%
“…The relative contribution of the AL and IL to the hor mone response was studied by selective blockade of either of the two lobes by DEX, which selectively inhibits secre tion from the corticotropes (AL) [19][20][21][22][23], or BR, which selectively inhibits the melanotropes (IL) via D2-receptor activation. DEX totally blocked the ACTH response to both types of stress whereas BR had no such effect.…”
Section: Discussionmentioning
confidence: 99%